2019
DOI: 10.1002/cam4.2454
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer cell‐derived exosomal miR‐20a‐5p promotes the proliferation and differentiation of osteoclasts by targeting SRCIN1

Abstract: Bone metastasis of breast cancer makes patients suffer from pain, fractures, spinal cord compression, and hypercalcemia, and is almost incurable. Although the mechanisms of bone metastasis in breast cancers have been studied intensively, novel specific target will be helpful to the development of new therapeutic strategy of breast cancer. Herein, we focused on the microRNA of tumor cell‐derived exosomes to investigate the communication between the bone microenvironment and tumor cells. The expression of miR‐20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 28 publications
(56 reference statements)
1
73
0
Order By: Relevance
“…Randall et al (52) reported that activation of FZD7, Of the genes identified in the present study that were consistent with those in the literature, only four miRNAs with MREs within ITGB8 were associated with cartilage degeneration and calcification, including miR-20a-5p, miR-145-5p, miR-93-5p and miR-17-5p. Guo et al (25) reported that miR-20a-5p in exosomes from breast cancer cells promoted the proliferation and differentiation of osteoclasts. Furthermore, Chen et al (53) revealed that decreased miR-145-5p expression promoted the proliferation of osteoclasts to aggravate cartilage erosion by targeting OPG.…”
Section: Discussionmentioning
confidence: 99%
“…Randall et al (52) reported that activation of FZD7, Of the genes identified in the present study that were consistent with those in the literature, only four miRNAs with MREs within ITGB8 were associated with cartilage degeneration and calcification, including miR-20a-5p, miR-145-5p, miR-93-5p and miR-17-5p. Guo et al (25) reported that miR-20a-5p in exosomes from breast cancer cells promoted the proliferation and differentiation of osteoclasts. Furthermore, Chen et al (53) revealed that decreased miR-145-5p expression promoted the proliferation of osteoclasts to aggravate cartilage erosion by targeting OPG.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, tumor cells have been shown to increase the number and activity of other cells. Breast cancer cell-derived exosomes can promote the proliferation and differentiation of osteoclasts through miRNA-20a-5p (Guo et al, 2019), and prostate cancer cell-derived exosomes exhibit strong promotion of osteoclastogenesis in vitro (Inder et al, 2014). This may contribute to the inherent mechanism through which patients with tumors exhibit osteoporosis.…”
Section: Exosomes Affect Osteoclast Differentiation and Activitymentioning
confidence: 99%
“…In addition, uptake of EVs enriched with miR-145 derived from colorectal cancer cells by macrophages increases their oncogenic effects via downregulation of histone deacetylase 11 (HDAC11) [ 79 ]. Guo et al found that exosomal transfer of miR-20a-5p released from breast cancer cells facilitate breast cancer development and metastasis [ 149 ]. They demonstrated that exosomal transfer of miR-20a-5p promotes migration of breast tumor cells to bone [ 149 ].…”
Section: Extracellular Mirnas Secreted From Cancer Cellsmentioning
confidence: 99%
“…Guo et al found that exosomal transfer of miR-20a-5p released from breast cancer cells facilitate breast cancer development and metastasis [ 149 ]. They demonstrated that exosomal transfer of miR-20a-5p promotes migration of breast tumor cells to bone [ 149 ]. In another study performed on breast cancer cells depicts that transfer of extracellular miR-375 from tumor cells to TAMs induced their migration and infiltration [ 71 ].…”
Section: Extracellular Mirnas Secreted From Cancer Cellsmentioning
confidence: 99%